Evidence of hawking (falconry) from bird and mammal bones - Prummel, W. (1997)
This paper deals with the archaeozoological and archaeological evidence for hawking, or falconry. The methods and history of hawking in Europe are described, after which five types of evidence for hawking are discussed. These are illustrated with material from the Slavonic stronghold of Oldenburg in Ostholstein, in the north of Germany, dated to AD 750-1150. (C) 1997 by John Wiley & Sons, Ltd.